Comparative sensitivity of field and laboratory populations of Hyalella azteca to the pyrethroid insecticides bifenthrin and cypermethrin - Clark, Stephen L.; Ogle, R. Scott; Gantner, Andrew; Hall Jr, Lenwood W.; Mitchell, Gary; Giddings, Jeffrey; McCoole, Matthew; Dobbs, Michael; Henry, Kevin; Valenti, Ted (Environmental toxicology and chemistry, 2015)
Hyalella azteca are epibenthic invertebrates that are widely used for toxicity studies. They are reported to be more sensitive to pyrethroid insecticides than most other test species, which has prompted considerable use of this species in toxicity testing of ambient surface waters where the presence of pyrethroids is suspected. However, resident H. azteca have been found in some ambient water bodies reported to contain surface water and/or sediment pyrethroid concentrations that are toxic to laboratory reared H. azteca. This observation suggests differences in the sensitivities of laboratory reared and field populations of H. azteca to pyrethroids. The goal of the present study was to determine the sensitivities of laboratory reared and field populations of H. azteca to the pyrethroids bifenthrin and cypermethrin. Specimens of H. azteca were collected from resident populations at field sites that are subject to varied land‐use activities as well as from laboratory populations. These organisms were exposed to bifenthrin‐ or cypermethrin‐spiked water in 96‐h water‐only toxicity tests. The resulting data demonstrated that: 1) field‐collected populations in urban and agricultural settings can be >2 orders of magnitude less sensitive to the pyrethroids than laboratory reared organisms; 2) field‐collected organisms varied in their sensitivity (possibly based on land‐use activities), with organisms collected from undeveloped sites exhibiting sensitivities similar to laboratory reared organisms; and 3) the sensitivity of field‐collected “tolerant” organisms increased in subsequent generations reared under laboratory conditions. Potential mechanisms for these differences are discussed. Environ Toxicol Chem 2015;34:2250–2262. © 2015 SETAC